2021
DOI: 10.1016/j.chemosphere.2020.128415
|View full text |Cite
|
Sign up to set email alerts
|

Microplastics in real wastewater treatment schemes: Comparative assessment and relevant inhibition effects on anaerobic processes

Abstract: The occurrence, fate and removal of microplastics (MPs) in a wastewater treatment plant (WWTP) in Central Italy were investigated together with their potential adverse effects on anaerobic processes. In the influent of the WWTP, 3.6 MPs . L -1 were detected that mostly comprised polyester fibers and particles in the shape of films, ranging 0.1-0.5 mm and made of polyethylene and polypropylene (PP). The full-scale conventional activated sludge scheme removed 86% of MPs, with the main reduction in the primary an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
26
1
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(42 citation statements)
references
References 52 publications
5
26
1
6
Order By: Relevance
“…Several mechanisms have been proposed; i.e., a lower residence time for smaller MP than for larger plastic debris (Enders et al 2015), small MP fragment in much higher abundance than large ones (Wang et al 2018) and aggregation and settling into the sludge for the lowest sizes (van den Berg et al 2020). Furthermore, the MPs percentage smaller than 500 µm increased from the INF (18.63%) to the EFF (21.43%), after UV disinfection, similar to those results reported after chemical disinfection, with a degradation level depending on contact time, temperature, and disinfectant concentration (Dris et al 2015;Pittura et al 2021).…”
Section: Resultssupporting
confidence: 85%
“…Several mechanisms have been proposed; i.e., a lower residence time for smaller MP than for larger plastic debris (Enders et al 2015), small MP fragment in much higher abundance than large ones (Wang et al 2018) and aggregation and settling into the sludge for the lowest sizes (van den Berg et al 2020). Furthermore, the MPs percentage smaller than 500 µm increased from the INF (18.63%) to the EFF (21.43%), after UV disinfection, similar to those results reported after chemical disinfection, with a degradation level depending on contact time, temperature, and disinfectant concentration (Dris et al 2015;Pittura et al 2021).…”
Section: Resultssupporting
confidence: 85%
“…However, MPs can have potential adverse effects on anaerobic processes, which normally yield biogas as a useful side-product. Thus, L. Pittura et al [142] have shown that in their case the presence 50 polypropylene MPs per g of solid led to a decrease of the methanogenic activity by 58%. This "poisoning" of the anaerobic microorganisms may be due to leachates from the MPs, which contain small organic molecules but also heavy metals.…”
Section: Microplastics In Sludgementioning
confidence: 94%
“…These can be anaerobic digestion or aerobic digestion/composting. Here, L. Pittura et al have shown that 86% of MPs (which included 100% of the particles and 87% of the fibers) can be retained with a pilot scale upflow granular anaerobic sludge blanket (UASB) in combination with an anaerobic membrane bioreactor (AnMBr) [142]. However, MPs can have potential adverse effects on anaerobic processes, which normally yield biogas as a useful side-product.…”
Section: Microplastics In Sludgementioning
confidence: 99%
See 1 more Smart Citation
“…(Lenz et al, 2015). Por ejemplo, es muy común el uso de antioxidantes en polímeros tales como PP y PS (Pittura et al, 2021). El Anexo VI muestra los espectros de distintos MP aislados y sus polímeros de referencia.…”
Section: Consideraciones Generales: Micropartículas Y Microplásticosunclassified